1989
DOI: 10.1073/pnas.86.11.4249
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of cDNA encoding Sm autoantigen: derivation of a cDNA for a B polypeptide of the U series of small nuclear ribonucleoprotein particles.

Abstract: The Sm snRNPs play a central role in the processing of pre-mRNA. Anti-Sm antibodies, the diagnostic hallmark of systemic lupus erythematosus, target the B/B and D polypeptides of these snRNPs. We have used patient autoantibodies to clone a cDNA from a human fibroblast cDNA library that encodes the full length of a polypeptide identical with, or closely related to, polypeptide B. This cDNA is comprised of 1139 bases and contains an open reading frame of 855 nucleotides that is capable of encoding 285 amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In support of this hypothesis is the deduced amino acid sequence of the B/B' subunit of Sm and HIV-1 gag polypeptide. Both molecules contain several regions rich in proline residues (11,12,13), a potential site for cross-reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this hypothesis is the deduced amino acid sequence of the B/B' subunit of Sm and HIV-1 gag polypeptide. Both molecules contain several regions rich in proline residues (11,12,13), a potential site for cross-reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins were extracted by incubation of the snRNPs with DE53 ion-exchange resin in the presence of EDTA. The molecular masses of the proteins derived from their cDNA sequences are 31.3 (A), 28.5 (A'), 25.5 (B"), 24.6 (B'), 23.7 (B), 13.4 (D1), 13.5 (D2), 13.9 (D3), 10.8 (E), 9.7 (F) and 8.5 kDa (G) Hermann et al, 1995;Lehmeier et al, 1994;Ohosone et al, 1989;Rokeach et al, 1988;Sillekens et al, 1987Sillekens et al, , 1989Sharpe et al, 1989;Stanford et al, 1988;van Dam et al, 1989).…”
mentioning
confidence: 99%
“…Human SnRNP core protein SmB/B Another clone obtained by the two-hybrid system is identical to the human SnRNP core protein SmB/B [31]. As for the SmD1 protein, Pu et al also demonstrated an interaction of in vitro translated SmB/B with ICln Xenopus [14].…”
Section: Human Snrnp Core Protein Smd1mentioning
confidence: 97%